Comparison of alaryngeal voice and speech - Globlek, Dubravka (Array, 2004)
The aim of the research was to compare voice and speech in three groups of alaryngeal speakers: 1. patients using esophageal speech, 2. patients with electroacoustical speech aid and 3. patients with voice prosthesis. Acoustic analysis and pronunciation tests were used for the analysis.